2001
DOI: 10.1017/cbo9780511545986
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gas Geochemistry

Abstract: Noble Gas Geochemistry Minoru Ozima, Frank A. PodosekNoble Gas Geochemistry discusses the fundamental concepts of using noble gases to solve problems in the earth and planetary sciences. The discipline offers a powerful and unique tool in resolving problems such as the origin of the solar system, evolution of the planets, earth formation, mantle evolution and dynamics, atmospheric degassing and evolution, ocean circulation, dynamics of aquifer systems, and numerous applications to other geological problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
603
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(630 citation statements)
references
References 0 publications
25
603
1
1
Order By: Relevance
“…7c) and increase with 4 He/ 40 Ar * . High CO 2 /noble gas ratios can occur in the residues of diffusion controlled degassing (Ozima and Podosek, 1983;Burnard, 2001) but would not produce elevated 4 He/ 40 Ar * and should be accompanied by higher δ 13 C and possibly decreased 3 He/ 4 He (Burnard et al, 2003), neither of which are observed. A more plausible explanation is that the vesicles are enriched in CO 2 .…”
Section: Evolution Of Vesicle Gasmentioning
confidence: 99%
“…7c) and increase with 4 He/ 40 Ar * . High CO 2 /noble gas ratios can occur in the residues of diffusion controlled degassing (Ozima and Podosek, 1983;Burnard, 2001) but would not produce elevated 4 He/ 40 Ar * and should be accompanied by higher δ 13 C and possibly decreased 3 He/ 4 He (Burnard et al, 2003), neither of which are observed. A more plausible explanation is that the vesicles are enriched in CO 2 .…”
Section: Evolution Of Vesicle Gasmentioning
confidence: 99%
“…where r is the ( 4 He/ 20 Ne) Air /( 4 He/ 20 Ne) measured and that of ( 4 He/ 20 Ne) Air is 0.318 (Ozima and Podosek, 1983). As far as the concentrations of trace elements (Table 2) are concerned, the highest values were measured in the Na + -Cl − waters and they were dominated by Fe, As and Ba (9620, 6170 and 3300 μg/L, respectively), followed by Mn (from 2.1 to 876 μg/L), Sb (from 1.1 to 326 μg/L), Zn (from 0.8 to 107 μg/L), Cu (from 3.4 to 48 μg/L), Ni (from 0.1 to 27 μg/L) and Co (from 0.3 to 11 μg/L).…”
Section: Chemical and Isotopic Analysis Of Dissolved And Bubbling Gasesmentioning
confidence: 99%
“…We use endmember d 15 N values for these components of 0& (Ozima and Podosek, 2002), À5 ± 2& (Marty, 1995;Cartigny et al, 1998;Sano et al, 1998;Marty and Zimmermann, 1999;Sano et al, 2001), and +7 ± 4& (Peters et al, 1978;Bebout and Fogel, 1992;Boyd and Pillinger, 1994;Bebout, 1995;Kienast, 2000;Sadofsky and Bebout, 2004;Li and Bebout, 2005) for atmosphere, upper mantle, and subducted hemipelagic sediments, respectively. An additional potential contributor of nitrogen to arc gases is the subducted altered oceanic crust; its d 15 N value, however, is currently poorly constrained but may be as low as À2.9& (Li et al, 2003).…”
Section: Gas Provenance: Resolution Into Endmembersmentioning
confidence: 99%
“…Despite the overwhelming presence of nitrogen in air, it is still possible to identify contributions from these other reservoirs because each has a distinctive chemical and isotopic nitrogen signature (Peters et al, 1978;Marty, 1995;Giggenbach, 1996;Marty and Humbert, 1997;Fischer et al, 2002;Ozima and Podosek, 2002). Nitrogen is therefore an excellent tracer of arc-related processes, as it is capable of fingerprinting gas sources and quantifying relative contributions to the volatile cycle at subduction zones Hilton et al, 2002).…”
Section: Introductionmentioning
confidence: 99%